2020
DOI: 10.1037/vio0000254
|View full text |Cite
|
Sign up to set email alerts
|

Changing perception: A randomized controlled trial of emotion recognition training to reduce anger and aggression in violent offenders.

Abstract: Objective:To determine whether emotion recognition training, which previously proved to be effective in adolescents, also reduces anger and aggression in adult violent offenders. Method:Detained male adults were randomized to complete either a 1-week computer training designed to promote the perception of happiness over anger in ambiguous facial expressions (n = 46), or a sham training control procedure (n = 44). Outcome measures were collected immediately after training and at 6-week follow-up, and included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…For example, it was found that aggressive, hostile, and prosocial behaviours did not change after a one-week emotional recognition training. 22 , 37 Our results may provide new insights into the discrepancies among previous findings. In the present study, the overall aggression level of juvenile delinquents did not change significantly, while training only reduced hostility.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, it was found that aggressive, hostile, and prosocial behaviours did not change after a one-week emotional recognition training. 22 , 37 Our results may provide new insights into the discrepancies among previous findings. In the present study, the overall aggression level of juvenile delinquents did not change significantly, while training only reduced hostility.…”
Section: Discussionmentioning
confidence: 59%
“… 14 , 17 Similar results were also found in a study that adopted a one-week training procedure, which revealed that the training effect remained six weeks later. 37 In addition to angry faces, a study on sad and fearful faces found that two or three sessions of training could bias the recognition of negative faces to positive faces. 38 In the present study, we found that the first day of training could induce a large change in the bias point and that the training effect changed slightly in the remaining days of training, indicating that the amount of training had little influence on the training effect.…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned argument on shared method variance could also explain these null results, although-again-the performance based measures did not correlate and previous studies do show that emotion recognition deficits are related to self-reported aggression (for a review, see [Smeijers et al, 2019]). Studies have even assessed the potential beneficial effects of training emotion recognition or response inhibition (Hubble et al, 2015), their results suggest that performance does improve but that it does not always result in less aggressive behavior (Kuin et al, 2020). In line with recommendations made by Grynberg et al (2012), an emotion recognition paradigm with morphed faces was used to limit perceptual information available for emotion identification.…”
Section: Exploratory Modelsmentioning
confidence: 99%
“…For instance, impaired emotion recognition facilitates violent behavior and recidivism in criminal offenders (Leshem et al, 2019). In addition, research has shown that subsequent crime was greatly reduced by improving facial emotion recognition in offenders (Hubble et al, 2015;Kuin et al, 2019;Timmermann et al, 2017). However, most previous evidence has focused on basic emotions, and no study to date has investigated complex social emotions.…”
Section: Introductionmentioning
confidence: 99%